Effect of Isotretinion on Rat’s Liver and Aptness of Cumin Oil in Protection - Tawfiq , Prshang; Yousif Sharef, Tuqa; Anwar Ali , Khabat; Sardar Salih , Lana (Diyala Journal of Medicine, 2020)
Background: Isotretinoin is a vitamin derivative also known as 13-cis-retinoic acid used in the treatment of severe acne and some forms of skin, head and neck cancer. Some studies have shown that isotretinoin induces apoptosis in various cells in the body. Isotretinion has not been clearly implicated in cases of clinically apparent acute liver injury with jaundice. The mechanism by which isotretinoin causes serum aminotransferase elevations is not known, but it may represent a direct toxic effect, in that it appears to be more frequent with higher dose therapy. For prevention or healing natural herb and its oil are used. The Cumin oil is one of these herbal oils which used as antioxidant and anti-inflammatory. Objective: To evaluate the histological damage of liver after treatment with the Isotretinoin and find out if cumin oil which was anti-inflammatory natural herb can protect liver from damage. Patients and Methods: 30 male wistar rats weighing 200-250g were used in this study divided into five groups: the first group was control, second was treatment group (T1), receive 10 mg of Isotretinion; the third group was (T2) receives 20 mg of Isotretinion. And last two others were cumin oil groups including (T3) receive 10 mg of Isotretinion plus Cumin oil and (T4) receive 20 mg of Isotretinion plus Cumin oil. The experiment was accomplished in three weeks. In the end of each week, animals from each group were killed and dissect and liver taken for histopathological study. Blood collected for liver functional enzymes evaluation. Liver functional enzymes include alkaline phosphatase, S-GOT, S-GPT, T.S.B, Bilirubin direct and Bilirubin indirect. Results: The study results show a significant difference between the control groups and treatment (T1) group in the values of alkaline phosphatase. A significant difference also found in the result of serum GOT between the T2, T3and T4 groups. The T3 group shows the highest significance between the other groups. The result of GPT shows no significant differences between the study groups except T3 group which show significant P˂0.05. The data of total serum bile (T.S.B) and indirect bilirubin test shows no significant differences among the study groups while analyzing data of direct bilirubin shows significant differences in T1and T2 comparing to other study groups graph. The histological examination of the rat’s liver shows variable changes in the treatment groups during different time of the study. Isotretinion affect the texture of liver tissue mains noticed alteration includes infiltration of inflammatory cell around central vein, congestion of sinusoid and vacuolar degeneration in hepatocytes the treated groups with cumin oil (T3 and T4) shows a type of tissue protection comparing to other groups (T1and T2). Conclusion: The present study conclude that long exposure to isotretinion cause hepatic damage, alteration in the liver texture and affect the functional liver enzyme level specially with high dose . Also the study concludes that the cumin oil is efficient in facing the toxicity effect of isotretinion and reverses the effect.